2011
DOI: 10.1128/aac.01005-10
|View full text |Cite
|
Sign up to set email alerts
|

Quaternized Chitosan Inhibits icaA Transcription and Biofilm Formation by Staphylococcus on a Titanium Surface

Abstract: Our previous study (Z. X. Peng et al., Carbohydr. Polym. 81:275-283, 2010) demonstrated that water-soluble quaternary ammonium salts, which are produced by the reaction of chitosan with glycidyl trimethylammonium chloride, provide chitosan derivatives with enhanced antibacterial ability. Because biofilm formation is believed to comprise the key step in the development of orthopedic implant-related infections, we further evaluated the efficacy of hydroxypropyltrimethyl ammonium chloride chitosan (HACC) with dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
67
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(71 citation statements)
references
References 50 publications
4
67
0
Order By: Relevance
“…For multidrug-resistant bacteria, however, particularly gentamicin-resistant bacteria, gentamicin-loaded PMMA has proven inadequate for treating or preventing infections. As reported in our previous work, HACC with 26% DS in PMMA bone cements exhibited predictable release kinetics and antibacterial activity for staphylococci (19,20). In the present study, we further demonstrate the effectiveness of HACC-loaded PMMA in treating bacterial infections in the tibial metaphysis in an animal model.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…For multidrug-resistant bacteria, however, particularly gentamicin-resistant bacteria, gentamicin-loaded PMMA has proven inadequate for treating or preventing infections. As reported in our previous work, HACC with 26% DS in PMMA bone cements exhibited predictable release kinetics and antibacterial activity for staphylococci (19,20). In the present study, we further demonstrate the effectiveness of HACC-loaded PMMA in treating bacterial infections in the tibial metaphysis in an animal model.…”
Section: Discussionsupporting
confidence: 62%
“…To improve the antibacterial activity and solubility of chitosan, quaternary ammonium chitosan derivatives have been synthesized, and their antibacterial activities have demonstrated significant increases with increasing alkyl substituent chain length (17)(18)(19)(20)(21). We synthesized a new quaternized chitosan derivative (hydroxypropyltrimethyl ammonium chloride chitosan [HACC]) that contains a series of quaternary ammonium substitutions, and we found that the antibacterial activities of HACC were enhanced as the quaternary ammonium degree of substitution (DS) increased (18)(19)(20). In vitro studies demonstrated that HACC-loaded PMMA (PMMA-H) bone cement exhibited strong antibacterial activity and good biocompatibility with osteogenic cells (20,21).…”
Section: Nfection Of Open Fractures Which Occurs In Approximately 24%mentioning
confidence: 99%
“…There are many reports on the activities of natural compounds on staphylococcal biofilm formation. Hydroxypropyltrimethyl ammonium chloride chitosan inhibits biofilm formation as well as expression of the icaA gene (40). Providone iodine also inhibits biofilm formation and decreases transcription of the ica operon (38).…”
Section: Discussionmentioning
confidence: 99%
“…A standard curve with known concentrations of gentamicin (Sigma-Aldrich) was used to determine the unknown concentrations. [21][22][23] Our previous study demonstrated that the three tested strains were biofilm-producing bacterial strains. 21,24 Bacterial adhesion assay using the spread plate method…”
Section: Characterization Of Drug Release From Tntsmentioning
confidence: 99%